Technical implementation and study of an experimental stand of an autonomous power supply system with a switched reluctance generator at variable speed - Mazurenko, L.; Dzhyra, O.; Shykhnenko, M.; Bilyk, O.; Gorodetsky, V. G. (Energy and Automation, 2025)
An experimental stand of an autonomous power supply system based on a DC machine simulating a variable speed prime mover and a switched reluctance generator is considered. Generalized and complete structural diagrams of the experimental stand are presented. The operating principle of individual structural elements of the stand is described. The process of self-excitation of a generator from a residual flux is considered and an oscillogram of this process is presented, illustrating the nature of the change in the output DC voltage. Using the oscillogram of the phase current of the generator, the movement of energy in the electric machine – semiconductor converter system is considered. The operating characteristics of a switched reluctance generator were investigated. The experimental data confirm the possibility of using the stand as an autonomous power supply system at variable speed. Key words: DC motor, switched reluctance generator, generated power